Young and outraged protesters? The Colombian social mobilization in 2011 - Acevedo Tarazona, Álvaro; Correa Lugos, Andrés David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
The cultural revolution of 1968 has made great impacts on the world. One of the main ones is the consolidation of youth as a target population with civic and political conscience, and concerned about future, not only in their local realities but at a global level. Repression and silencing put into practice by the States under the excuse of the national security makes that phenomenon almost disappear in the following decades. It would take more than five decades for young people around the world would share again the passion for civic and political responsibility on the entire planet. In Colombia this phenomenon was lived with the Mane and it was the prelude to new forms of collective action within a population facing an incipient peace process. The purpose of this article is to reflect on the role of youth in contemporary collective processes and their importance as agents of change and civil awareness.